1990
DOI: 10.1002/1097-0142(19901115)66:10<2239::aid-cncr2820661034>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in the families of children with soft tissue sarcoma

Abstract: The cancer experience among 754 first-degree relatives (mothers, fathers, and siblings) of a population-based series of 177 children with soft tissue sarcoma is reported. The current study represents an extension of our earlier work in which the authors found an excess of breast cancer in the mothers of 143 of these children. There were 40 cancers among all first-degree relatives, compared with 24.82 expected (relative risk [RR] 1.61, P = 0.006). There was no excess in fathers, but an excess of borderline sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…However, preliminary data do exist that could provide some guidance. On the basis of population studies of cancer risks in families of children with sarcoma and follow-up studies in families with LFS, it has been shown that the risk of cancer is elevated up to, but not beyond, age 60 years (Birch et al, 1990;Garber et al, 1991). Using a data set comprising details of occurrence of cancer among the close relatives of a hospital-based series of children who had survived sarcoma, Lustbader et al (1992) conducted a segregation analysis.…”
Section: Genotype-phenotype Correlations and Penetrancementioning
confidence: 99%
“…However, preliminary data do exist that could provide some guidance. On the basis of population studies of cancer risks in families of children with sarcoma and follow-up studies in families with LFS, it has been shown that the risk of cancer is elevated up to, but not beyond, age 60 years (Birch et al, 1990;Garber et al, 1991). Using a data set comprising details of occurrence of cancer among the close relatives of a hospital-based series of children who had survived sarcoma, Lustbader et al (1992) conducted a segregation analysis.…”
Section: Genotype-phenotype Correlations and Penetrancementioning
confidence: 99%
“…Mutations in p53 have also been found in nearly 50% of RMS cases and cell lines (Mulligan et al, 1990;Felix et al, 1992;Merlino and Helman, 1999). Furthermore, association with a p53 germline mutation has been reported in a childhood RMS case (Birch et al, 1990) and in families predisposed to this malignancy (Malkin et al, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…There is an established excess risk of breast cancer for the mothers of children with a sarcoma (Li et al, 1969;Birch et al, 1984Birch et al, , 1990Strong et al, 1987). Buirki et al (1987) found an excess of sarcomas in the brothers of breast cancer patients.…”
mentioning
confidence: 99%